Fragmented nature
1 online resource (vi, 219 pages)
Keywords: "The Latin Middle Ages were characterised by a vast array of different representations of nature. These conceptualisations of the natural world were developed according to the specific requirements of many different disciplines, with the consequent result of producing a fragmentation of images of nature. Despite this plurality, two main tendencies emerged. On the one hand, the natural world was seen as a reflection of God's perfection, teleologically ordered and structurally harmonious. On the other, it was also considered as a degraded version of the spiritual realm - a world of impeccable ideas, separate substances, and celestial movers. This book focuses on this tension between order and randomness, and idealisation and reality of nature in the Middle Ages. It provides a cutting-edge profile of the doctrinal and semantic richness of the medieval idea of nature, and also illustrates the structural interconnection among learned and scientific disciplines in the medieval period, stressing the fundamental bond linking together science and philosophy, on the one hand, and philosophy and theology, on the other. This book will appeal to scholars and students alike interested in Medieval European History, Theology, Philosophy, and Science"--